2005
DOI: 10.2224/sbp.2005.33.8.735
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Identity Re-Creation in the Context of Internet Dating

Abstract: This research explored the identity re-creation process as it occurs via the consumption of Internet dating services. Informants were interviewed about how they use their posted dating profiles to explore aspects of their own identities and about the perceived impact that online and offline feedback to these profiles have upon their identities. Informants' responses indicated that individuals can re-create their identities through the use of Internet dating services. Furthermore, online and offline validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
73
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 23 publications
0
73
0
4
Order By: Relevance
“…It seems that the introverts do not behave similarly as they usually do in offline life, that is, inclining to withdraw from active self-expression. The authors explain that this may probably be due to the absence of non-verbal cues and the better control over the pace of interaction.Recent studies on less anonymous online platforms such as Internet dating sites and SNSs showed that identity production on these platforms differs from those constructed on the anonymous ones mentioned earlier Gibbs et al, 2006;Manago et al, 2008;Yurchisin et al, 2005;Zhao et al, 2008). A study based on content analysis of Facebook users found that unlike users of anonymous platforms (e.g.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…It seems that the introverts do not behave similarly as they usually do in offline life, that is, inclining to withdraw from active self-expression. The authors explain that this may probably be due to the absence of non-verbal cues and the better control over the pace of interaction.Recent studies on less anonymous online platforms such as Internet dating sites and SNSs showed that identity production on these platforms differs from those constructed on the anonymous ones mentioned earlier Gibbs et al, 2006;Manago et al, 2008;Yurchisin et al, 2005;Zhao et al, 2008). A study based on content analysis of Facebook users found that unlike users of anonymous platforms (e.g.…”
mentioning
confidence: 96%
“…Many recent studies started to examine how people present themselves on less anonymous platforms such as online dating sites and social networking sites (SNSs) (e.g. Manago et al, 2008;Yurchisin, Watchravesringkan, & McCabe, 2005;Zhao, Grasmuck, & Martin, 2008). The results of these studies showed that people's practices of identity production in these less anonymous platforms differ from those early anonymous ones.…”
mentioning
confidence: 99%
“…[1][2][3][4] Extant empirical literature indeed shows that identity markers on SNSs such as profilers' photos and numbers of friends listed can play a role in impression formation. [5][6][7][8][9][10] The present study focuses on the possible boundaries to the articulation of possible selves through SNSs.…”
mentioning
confidence: 99%
“…In their exploratory, ethnographic study on identity re-creation, Yurchisin, Watchravesringkan, and Brown McCabe (2005) found that although most participants sought to be honest and truthful in their profiles, they also admitted to exaggerating the truth a bit.…”
mentioning
confidence: 99%
“…Although studies have been done on how online dating participants manage their online presentations with a view to meeting others in person (Bargh et al, 2000;Ellison et al, 2006;Hardey, 2002, Hardey, 2004Yurchisin et al, 2005), only one (Toma, Hancock, & Ellison, 2008) so far has compared participants' actual characteristics with their reported (true and ideal) characteristics.…”
mentioning
confidence: 99%